การศึกษาบทบาทของพยาบาลเวชศาสตร์ความดันบรรยากาศสูง - ปรียา ขาวงาม (วารสารพยาบาลทหารบก, 2021)
The purpose of this research was to study the roles of hyperbaric nurses. The Ethnographic Delphi Future Research (EDFR) was applied. The subjects included 25 experts including 7 physicians involved in HBOT, 7 nursing administrators of HBOT, 4 nursing educators of HBOT and 7 staff nurses of HBOT. The EDFR consisted of three steps: In step one, describe to roles of hyperbaric nurses from the experts. In step two, the data were analyzed by using content analysis for developing the rating scale questionnaire. In step three, The data were analyzed again by using median and interquartile range to summarize the roles of hyperbaric registered nurses. The results showed the roles of hyperbaric nurses consist of 7 roles as follows: 1) The nursing practice roles including patient care of HBOT comprehensive holistic by nursing process 11 items. 2) The educator roles in the teaching process to the individual patient, family, etc. including 9 items. 3) The development and innovative nursing roles including 3 items. 4) The role of the nurse manager to assess the risk management 7 items. 5) The counselor roles of HBOT services regarding advising patients and those interested 6 items. 6) The role of the coordinator services regarding coordination with the staff and relevant departments 6 items. 7) The role of patient advocacy including 7 items.